Evil radioactivity - Freudenberg, L. S.; Beyer, T.; Müller, S. P.; Görges, R.; Hopfenbach, A.; Bockisch, A. (Nuklearmedizin - NuclearMedicine, 2006)
Aim: We assess the perspective of patients with thyroid disease towards radiation and radioactivity by means of a cultural- anthropological approach based on qualitative measures and quantitative scores. From the interviews with the patients we evaluate as to how much radioactivity is accepted as an abstract term or as a benefit within the medical context. Patients, methods: 68 patients with autonomously functioning thyroid lesions (35 women, 33 men, 32-81 years) were included in this study. All patients were interviewed in an open dialogue with the principal investigator. Patients were asked to describe their attitude towards radioactivity in general and towards radioiodine therapy in particular. Patients were asked to use a scoring system (1 = positive, 5 = negative) to quantify their attitudes. Results: The responses of all patients towards radioactivity in general were heterogeneous with most responses reflecting a negative perception. Many patients expressed their associated fears about atomic energy, malignant diseases and radioactive contamination. The scoring system reflected a mostly negative opinion base. However, patients became more positive once they assumed an immediate benefit of radioactivity for the treatment of their own disease (p = 0.01). Conclusions: Knowing about significant differences in patient’s perception about radioactivity in general or in the clinical context may help to optimise and tailor the initial, pre-therapeutical interview towards the patient.
Keywords: Radiation; perception; radioiodine therapy; cultural anthropology; medical anthropology